Sunk cost hysteresis and hysteresis losses - Adamonis, Jolita; Justus Liebig University Giessen (My University, 2017)
The transition from one economic equilibrium to another as a consequence of shocks is often associated with sunk adjustment costs. Firm-specific sunk market entry investments (or sunk market exit costs) in case of a reaction to price shocks are an example. These adjustment costs lead to a dynamic supply pattern similar to hysteresis. In analogy to hysteresis losses" in ferromagnetism, we explicitly model dynamic adjustment losses in the course of market entry and exit cycles. We start from the micro level of a single firm and use explicit aggregation tools from hysteresis theory in mathematics and physics to calculate dynamic losses. We show that strong market fluctuations generate disproportionately large hysteresis losses for producers. This could offer a reason for the implementation of stabilizing measures and policies to prevent strong (price) variations or alternatively - reduce the sunk entry and exit costs. However, the explicit inclusion of uncertainty (associated with an option value of waiting) is shown to reduce economic hysteresis losses. Based on theoretical considerations of hysteresis losses, this manuscript also introduces a new measure (an indicator) to capture hysteresis losses empirically. As examples, the most important German export sectors to the U.S. and Italian wine exports to the U.S. are investigated. In both cases, the theoretical findings of over-proportionally large hysteresis losses compared to the changes in forcing variable could be approved.
Sunk Cost Hysterese und Hysterese-Verluste
Keywords: Sunk Costs; Hysterese; Hysterese-Verluste; Pfadabhängigkeit; Preisach; Sunk Costs; Hysteresis; Hysteresis Losses; Path-dependence; Preisach; ddc:330